2008
DOI: 10.14221/ajte.2008v33n3.5
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Partnerships : A Model for Science Teacher Education and Professional Development

Abstract: This paper proposes a collaborative partnership between practicing and pre-service teachers as a model for implementing science teacher education and professional development. This model provides a structure within which partnerships will work collaboratively to plan, implement and reflect on a series of Science lessons in cycles of actionreflection adapted from Korthagen's (2001) ALACT model. Issues within Science education, teacher professional development and teacher education are considered in the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…In conclusion, the triadic partnership approach can promote increased motivation, confidence and awareness of science pedagogies and lead to professional benefits for the inservice teacher participants and these findings are consistent with earlier research (Jones, 2008;Kenny, 2009;Murphy et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, the triadic partnership approach can promote increased motivation, confidence and awareness of science pedagogies and lead to professional benefits for the inservice teacher participants and these findings are consistent with earlier research (Jones, 2008;Kenny, 2009;Murphy et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other research on partnership based programs which reported professional development for in-service teachers who participate in them (Jones, 2008;Murphy et al, 2008). A range of data was collected from principals and teachers who participated in the project and this data has been analysed in relation to the following research question: What perceived benefits did the participating colleague primary teachers and principals associated with their participation in the triadic partnership approach to teaching science in their classrooms?…”
Section: The Key Elements Of the Triadic Partnership Approachsupporting
confidence: 91%
See 1 more Smart Citation
“…The effects on the confidence of the pre-service teachers, reported in detail in XXXX (2009), were also consistent with other examples of collaborative professional learning experiences in science (Jones, 2008;Murphy, Beggs, Carlisle & Greenwood, 2008). The question of whether involvement in the project actually led to any sustained long-term change in practice in terms of science teaching will be the subject of further research.…”
Section: Discussionsupporting
confidence: 66%
“…The activities were developed collaboratively by the R/F and the teachers. The advantage of this process was that it provided opportunities for the partners to bring their expertise to this collaboration (see Jones, 2008). The initial idea was to motivate the teachers by making them members of an action research group, meaningfully engaging them in the development of the activities and the instruction material (Kallery & Fragonikolaki, 2007).…”
Section: Activities Development: Approach and Proceduresmentioning
confidence: 99%